2016
DOI: 10.4103/1305-7456.175699
|View full text |Cite
|
Sign up to set email alerts
|

Changes in jawbones of male patients with chronic renal failure on digital panoramic radiographs

Abstract: Objective:To compare the existence of gonial cortical bone thickness, antegonial index, mandibular canal bone resorption and gonial angle values and pathologies like ground-glass appearance in jawbones and brown tumor in male patients undergoing dialysis due to chronic renal failure and men from the healthy control group on panoramic radiographs.Materials and Methods:Panoramic radiographs were taken from 80 male individuals in total (40 normal and 40 dialysis patients). Values obtained from the right and left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
3
4
0
2
Order By: Relevance
“…Dagistan et al found a significant decrease in antegonial index, gonial cortical bone thickness, and gonial angle values in chronic renal failure patients. Additionally, mandibular canal wall resorption was also statically significant (18). Similarly, in this study we found a significant difference between cases and controls in mandibular cortical thickness.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Dagistan et al found a significant decrease in antegonial index, gonial cortical bone thickness, and gonial angle values in chronic renal failure patients. Additionally, mandibular canal wall resorption was also statically significant (18). Similarly, in this study we found a significant difference between cases and controls in mandibular cortical thickness.…”
Section: Discussionsupporting
confidence: 67%
“…Incidence of CKD is 377 per million in the United States. CKD increases with age and males are more commonly affected than females (18). The dialysis patient's number in Iran is almost 13 000 and the renal transplant patient's number is almost 17 000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus among researchers regarding the use of panoramic radiograph as a reliable tool for the diagnosis of osteoporosis. 4 8 10 19 In this respect, studies indicate the MI and MCI to be the best parameters for the identification of osteoporosis on panoramic radiographs and reference values for mandibular cortical thickness of 3.0, 3.15, and 3.5 mm have been suggested for the study of osteoporosis. 2 4…”
Section: Discussionmentioning
confidence: 99%
“…Penilaian dilakukan secara visual dengan mengklasifikasikan bentuk morfologi korteks inferior mandibula sepanjang foramen mentalis hingga regio antegonial ke dalam tiga kategori: C1, margin endosteal dari korteks terlihat tajam dan tegas pada kedua sisi, menandakan bahwa korteks dalam kondisi normal dan tidak terjadi perubahan; C2, margin endosteal memiliki defek semilunar atau membentuk residu (satu hingga tiga lapisan) pada satu atau kedua sisi (mild to moderately eroded cortex); C3, lapisan kortikal membentuk endosteal dengan residu yang lebih tebal dan berporus dengan ketebalan yang berkurang (severely eroded cortex). 8,9,10 Pengukuran ketebalan kortikal mandibula menggunakan Antegonial Index dilakukan pada area yang terletak pada anterior sudut gonial, yakni berupa garis yang tegak lurus terhadap korteks pada garis yang menghubungkan batas anterior dari ramus ascendens hingga batas bawah mandibula. Pengukuran dilakukan pada sisi kanan dan kiri mandibular, yang kemudian diambil nilai rata-rata sebagai hasil akhir menggunakan software Image-J (National Institute of Health, Bethesda, MD, USA).…”
Section: Bahan Dan Metodeunclassified